Households’ Interest-bearing Assets - Jääskelä, J; Connolly, E; Fleming, F (My University, 2012)
Households invest around two-fifths of their financial assets in interest-bearing assets. These assets are predominantly held directly in deposits and also via superannuation and other investment funds. Deposits have grown strongly in recent years, although there has been no growth in interest-bearing securities. Compared with other advanced economies, interest-bearing assets represent a relatively small share of financial assets. For the household sector as a whole, interest-bearing assets are lower in value than debt, so household disposable income increases as interest rates decline. Interest-bearing assets tend to be held by retirees, while younger households are more likely to be in debt. Interest-bearing assets are expected to rise over time as the population ages.
Reserve Bank of Australia Bulletin
Bulletin
Keywords: Income & Finance -- Wealth; Intergenerational Transfer -- Wealth and Assets; Income, wealth and finances; Intergenerational transfer; Income & Finance; Intergenerational Transfer; Wealth; Wealth and Assets; Intergenerational transfer; Income, wealth and finances